Neuroeconomic foundations of trust and social preferences - Ernst Fehr; Urs Fischbacher; Michael Kosfeld (Institute for the Study of Labor (IZA), 2005)
This paper discusses recent neuroeconomic evidence related to other-regarding behaviors and the decision to trust in other people's other-regarding behavior. This evidence supports the view that people derive nonpecuniary utility (i) from mutual cooperation in social dilemma (SD) games and (ii) from punishing unfair behavior. Thus, mutual cooperation and the punishment of free riders in SD games is not irrational, but better understood as rational behavior of people with corresponding social preferences. We also report the results of a recent study that examines the impact of the neuropeptide Oxytocin (OT) on trusting and trustworthy behavior in a sequential SD. Animal studies have identified Oxytocin as a hormone that induces prosocial approach behavior, suggesting that it may also affect prosocial behavior in humans. Indeed, the study shows that subjects given Oxytocin exhibit much more trusting behavior, suggesting that OT has a direct impact on certain aspects of subjects' social preferences. Interestingly, however, although Oxytocin affects trusting behavior, it has no effect on subjects' trustworthiness.
Keywords: A13; C90; 330; social preferences; foundations of trust; neuroeconomic; Vertrauen; Soziale Wohlfahrtsfunktion; Neuroökonomie